Impact of interankle blood pressure difference on major adverse cardiovascular events in cryptogenic stroke patients without peripheral artery disease: a retrospective cohort study. Issue 2 (23rd February 2022) - Han, Minho; Baik, Minyoul; Kim, Young Dae; Choi, Junghye; Seo, Kangsik; Park, Eunjeong; Heo, Ji Hoe; Nam, Hyo Suk
Abstract : Objective: We investigated whether interankle blood pressure difference (IAND) can predict major adverse cardiovascular events (MACEs) in patients with cryptogenic stroke (CS) without peripheral artery disease (PAD). Design: A retrospective cohort study. Setting: Retrospective medical record data of patients with first-ever acute cerebral infarction who were admitted between 1 January 2007 and 31 July 2013. Participants: CS patients admitted within 7 days of symptom onset were included. Outcome measures: MACEs were defined as stroke recurrence, myocardial infarction occurrence, or death. Survival analyses were conducted using the Kaplan-Meier method and Cox regression analysis. Methods: Consecutive CS patients without PAD who underwent ankle–brachial index (ABI) measurements were enrolled. PAD was defined if a patient had an ABI of <0.90 or a history of angiographically confirmed PAD. Systolic and diastolic IANDs were calculated as follows: right ankle blood pressure—left ankle blood pressure. Results: A total of 612 patients were enrolled and followed up for a median 2.6 (interquartile range, 1.0–4.3) years. In the Cox regression analysis, systolic and diastolic IANDs ≥15 mm Hg were independently associated with MACEs in CS patients without PAD (hazard ratio (HR) 2.115, 95% confidence interval (CI) 1.230 to 3.635 and HR 2.523, 95% CI 1.086 to 5.863, respectively). In the subgroup analysis, systolic IAND ≥15 mm Hg was independently associated with MACEs in older patients (age ≥65 years) (HR 2.242, 95% CI 1.170 to 4.298) but not in younger patients (age <65 years). Conclusions: Large IAND is independently associated with the long-term occurrence of MACEs in patients with CS without PAD. In particular, the association between IAND and MACEs is only valid in elderly patients.